Pengaruh Preferensi Konsumen, Brand Trust dan Promosi Terhadap Keputusan Pembelian Pada Maxiking Chicken Nugget di Kota Medan - Putri, Rizki Adinda; Risal, Taufiq (ProBisnis : Jurnal Manajemen, 2025)
The study aims to determine and analyze the influence of consumer preference, brand trust, and promotion on the purchasing decision of Maxiking Chicken Nugget in Medan City, both partially and simultaneously. The research background is based on the phenomenon of declining sales of Maxiking Chicken Nugget during the 2021-2024 period, accompanied by low preference, low brand trust, and suboptimal promotional efforts. This research employs a quantitative method eith casual assosiative approach. The sample consists of 130 respondents selected using an accidental sampling technique. Data were collected through observation, interviews, and questionnares, while the data analysis used multiple linear regression, t-test, F-test, and coefficient of determination. The result show that: (1) Consumen preference partially has no positive and significant effect on purchasing decisions, (2) Brand trust partially has no positive and significant effect on purchasing decisions, (3) Promotion partially has a positive and significant effect on purchasing decisions, and (4) Consumer preference, brand trust, and promotion simultaneously have a positive and significant effect on purchasing decisions. The coefficient of determination indicates that the three independent variables contribute to the variation in purchasing decisions, while the remaining percentage is influenced by other factors beyond this study.